Deliberate ignorance choosing not to know - Engel, Christoph 1956-; Hertwig, Ralph (The MIT Press, 2020)
"Psychologists, economists, historians, computer scientists, sociologists, philosophers, and legal scholars discuss when is deliberate ignorance a virtue, and what type of environment does it require"-- Provided by publisher.